ANALYSIS OF GIRLS' PHYSICAL FITNESS INDICATORS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
: In order to increase the general physical fitness of female students, an experimental field was organized in the sports hall of Fergana State University.